Thread: Exercise 3.4
View Single Post
Old 11-10-2013, 04:27 PM
jamesclyeh jamesclyeh is offline
Junior Member
Join Date: Nov 2013
Posts: 1
Default Re: Exercise 3.4


For part (a), in one of the last steps I did:
Rearrange: \hat{\bf{y}}={\bf{y}}+H\epsilon
Since {\bf{y}}=Xw^*, \hat{\bf{y}}=Xw^*+H\epsilon

Are these steps correct?
I found subbing {\bf{y}}=Xw^* back in a bit recursive because I previously solved for w^* and plugged that in to get {\bf{y}}=H{\bf{y}}-H\epsilon.

Also for (b)
Is the answer \hat{\bf{y}}-{\bf{y}} = (H-I)\epsilon <---I ll delete this once its confirmed.

Reply With Quote